Zwierzęta w chińskim: wartościowania i tabu - Stria, Ida (Investigationes Linguisticae, 2012)
This work is the result of an ethnolinguistic research in the animal lexical area. The analysis is based on the notion of the linguistic picture of the world (LPW). One of the underlying elements of LPW is division of the world into taboo (the sacred) and noa (the profane). This division is reflected in various idiomatical expressions, which serve as the basis of this work. The aim of this study was to outline the system of values connected to animal symbolism. The author has analysed Chinese word combinations containing 6 zodiac animals. These animals seem to be an important part of Chinese culture with a high symbolic load. The Zodiac in the beliefs of the Chinese carries a positive meaning. However, the analysis of the idioms containing the names of the zodiac animals provides completely different conclusions. On the basis of the lexical material, it can be concluded that various types of symbolism are attributed to the zodiac animals in the Chinese language, not always resulting from their place in mythology.